Do Municipal Governments Need More Tax Powers? A Background Paper on Municipal Finance in Alberta - Melville McMillan; Bev Dahlby (The School of Public Policy Publications, 2014)
Local governments in Alberta have faced considerable and variable challenges over the past 60 years. For example, the rapid population and economic growth during the 1950s, ’60s and ’70s created exceptional demands for schools, schooling and municipal infrastructure; demands exceeding those of the last 30 years. Local and especially municipal financing has relied heavily on the property tax throughout. Questions are being asked today about whether the property tax is sufficient for municipal government. Our historical analysis provides insights into the fiscal situation of Alberta’s municipalities that can assist in addressing those questions. The main findings are highlighted here. We conclude that current demands, though considerable, are not creating stress on the property tax as a source of municipal revenue. • The property tax burden in Alberta during the past decade is the lowest that it has been over the past 60 years. Presently, property taxes are about 3.5 per cent of personal income. They were as high as seven per cent during much of the 1960s and averaged in the four to five per cent range from 1950 to 2000. Local and provincial school taxes were responsible for most of the fluctuations in the property tax burden. Municipal property taxes ranged from two to three per cent of personal incomes and recently amounted to about 2.5 per cent, a level typical of that over the past 20 years. • Investment in local infrastructure has over the past 30 years been at half the rate of that of the previous 30 years. Only since 2006, with the assistance of provincial capital grants, has infrastructure spending shown upward movement. Capital spending lagged population growth for many years and probably contributed to a deterioration of infrastructure. • Municipal current or operating expenditures (about three-quarters of the total) have been a declining share of personal incomes since the late 1980s and, since 2000, are a smaller share than observed since the early 1950s. • Since the mid-1990s, municipal total expenditures (current plus capital) have represented a smaller percentage of personal incomes than in any years since 1953.